Hubungan Pengetahuan Ibu Nifas Terhadap Gairah Seksual Di PMB L Kota Tangerang Tahun 2022 - Nita Sri Melati; Tetin Rismayanti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Background: Many women after giving birth have feelings of worry about having sex after childbirth, disappearing sexual arousal and other feelings of worry. This condition if left unchecked can cause disharmony in the family.Objective: This study aims to analyze the relationship between maternal knowledge and the emergence of post partum sexual arousal.Methods: Using cross sectional, it was carried out for 2 months starting from October to November 2022 postpartum mothers (0 - 40 days) in the PMB L work area in October-November with a total of 25 people.Result: 40% of mothers with high knowledge have high sexual arousal and only 6.7% have low sexual arousal, the P-Value = 0.006 < 0.05. This shows that good knowledge of postpartum mothers has a positive and significant influence on the emergence of sexual arousal. , the value of OR > 1 of 6.125 (0.979-38.312) strengthens the notion that good knowledge of postpartum mothers on post partum sexual arousal is a factor in whether or not there is sexual arousal in postpartum mothers..Conclusions: P-Value = 0.006 < 0.05. These results indicate that good knowledge of postpartum mothers on postpartum sexual arousal has a positive and significant influence/relationship on the emergence of postpartum women's sexual arousal, OR value > 1, which is 6.125 CI value / interval belief ( 0.979-38.312) the stronger the assumption that knowledge is a determinant of the emergence of post partum sexual arousal. It is hoped that midwife health workers can provide information on post partum care so that they can emphasize the types